Revocation of testamentary provisions. A comparative analysis between Peruvian law and Cuban law - Pelegrino Toraño, Luis Andrés (2022)
This article presents a comparative analysis between Peruvian law and Cuban law about the concept of revocation of testamentary provisions. This analysis is carried out in both legal systems, and studies, from an approach that combines the exegetical with the doctrinal and comparative analysis, the revocation as a legal concept, its characteristics and forms, as well as the gaps or regulatory gaps that exist in the Peruvian and Cuban law. The study shows the notable differences between both systems in the regulation of revocation, despite the similarities of their Civil Codes, as well as the need for regulatory reforms in the Cuban case.